Polynesian medicine used to treat diarrhea and ciguatera: An ethnobotanical survey in six islands from French Polynesia. (28th June 2022) - Chassagne, François; Butaud, Jean-François; Torrente, Frédéric; Conte, Eric; Ho, Raimana; Raharivelomanana, Phila
Abstract: Ethnopharmacological relevance: In French Polynesia, many pathologies common or endemic to the territory cause diarrhea. This is the case for rotavirus gastroenteritis, salmonella food poisoning, ingestion of water contaminated by bacteria, and ciguatera. To treat these ailments, the population may employ traditional medicine for cultural reasons, geographical isolation, and poor health coverage. Polynesian remedies are often used without medical consultation and there is no data on their benefit-risk balance. A few ethnobotanical studies have been carried out in order to identify the traditional remedies used for various ailments, but few studies have focused on gastrointestinal pathologies. In this context, an ethnobotanical survey was carried out to identify treatments used for diarrhea and ciguatera, inventory the plants used, better understand the local representation of these remedies, and provide efficacy and safety data on these uses. Materials and methods: From February to April 2021, a semi-structured survey was conducted on six islands in French Polynesia, including one island in the Windward Islands archipelago (Tahiti), three islands in the Marquesas archipelago (Hiva Oa, Nuku Hiva, Tahuata), and two islands in the Leeward Islands archipelago (Raiatea, Tahaa). A total of 133 people was interviewed including 34 specialists (of which 29 experts in herbalism). Results: These people mentioned the use of 27 plants for the treatment of diarrhea, and 24 for the treatment of ciguatera. Citrus aurantiifolia, Psidium guajava and Cordyline fruticosa were the three most cited plant species used for treating diarrhea, while Cocos nucifera, Punica granatum and Barringtonia asiatica were the most cited for ciguatera. A large majority of plants are widespread and introduced plants, which is congruent with the history of Polynesian people. While some plants are well known for similar uses (e.g. Psidium guajava for diarrhea, Heliotropium arboreum for ciguatera), others are less well known and may present toxicity risks (e.g. Barringtonia asiatica for ciguatera). Conclusion: Traditional Polynesian medicine is an integral part of the local culture so important to be preserved and valued. However, more pharmacological and toxicological studies are still needed to determine the benefit-risk balance of some of these remedies and to allow their official integration into the Polynesian health system. Graphical abstract: Image 1